Pendapatan Usahatani Menurut Jenis Tanaman Di Desa Lembah Asri Kecamatan Weda Selatan Kabupaten Halmahera Tengah - Alting, Danuarta; Waney, Nordy Fritsgerald Lucky; Mandei, Juliana Ruth (Sam Ratulangi University, 2024)
The aim of the research is to calculate and analyze the income from lowland rice, corn and orange farming in Lembah Asri Village. The research was carried out for 3 months, namely from August to October 2023, starting from preparation to preparing the research report. The data used in this research are primary and secondary data. Primary data was obtained in the research field, namely from interviews with lowland rice farmers, while secondary data was obtained from agencies related to the research. The sample used was purposive sampling (intentionally). The farmers sampled were 5 respondents for lowland rice farming, 5 respondents for corn and 5 respondents for Siamese orange farming. From the results of research conducted in Lembah Asri Village, South Weda District, Central Halmahera Regency, Siamese Orange Farming has a very large income, namely IDR27,233,140.6 per farmer with an R/C Ratio of 3.36, then followed by lowland rice farming with an income of IDR13,078,263 per farmer with an R/C Ratio of 3.94 and the lowest income is corn farming of IDR10,449,063.6 with an R/C Ratio of 3.94.